منهج الكتاب والسنة في التعامل مع المذنبين والمعاتبين بذكر ذكر أخطائهم لاأسمائهم - Abdoul Karim Toure; Mohd Yusuf Ismail; Abd Muhaimin Ahmad (Akademi Pengajian Islam, Universiti Malaya, 2024)
This study is an attempt bytheresearchersto know the methodology of theQur’anand Sunnahwhiledealing with individuals and groups of believers andnone believers whentheycommit an error,how the Qur’an and Sunnah mention those errors, eitherto give a hint orto mentionnames? What is the style of the Qur’an and Sunnahwhile mentioning errors from the two parties, the infidels and those who have faith? Didboth used the same style or eachhas its own unique style?Researchers have concluded afterfollowingalmost allverses and manyAhadith,thatthere is a different between the style of the Qur’an and the Sunnah. The Qur’an,in dealing with both believers and none believers,did not mention names of thosewhocommittederrors but gave hints,except for eight persons with reasons mentioned by the researchers. The Sunnah dealtalmost with believers only but categorisethem into senior companions, new believers and Bedouins, while being softwith the new believers and the Bedouins, the Prophetwas strictwith seniors when they commitan error. The researchers suggest that Muslimpreachers should follow the method of theQur’anand Sunnah in correcting theerrors of believersof all categories.